Recent results on elastic scattering and single-neutron stripping reaction in the 18O+48Ti collision at 275 MeV - Sgouros, Onoufrios; Brischetto, G. A.; Cappuzzello, F.; Cavallaro, M.; Carbone, D.; Agodi, C.; Calvo, D.; Chavez Lomeli, E. R.; Ciraldo, I.; Cutuli, M.; De Gregorio, G.; Delaunay, F.; et al. (HNPS Advances in Nuclear Physics, 2024)
A global study of the 18O+48Ti collision at 275 MeV was carried out within the NUMEN and NURE experimental campaigns by measuring the complete net of nuclear reactions which may be involved in the 48Ti→48Ca double charge exchange transition. The relevant experiment was visualized at the INFN-LNS in Catania, where angular distribution measurements for a plethora of reaction channels were performed by means of the MAGNEX large acceptance magnetic spectrometer. The present work provides an overview of the analyses of the elastic scattering and one-neutron transfer reaction channels.